Notice of Retraction: Perspective and Prediction of the Rule of High Temperature Melting of SiO₂ via Visual Analysis - Yinghao Zhu; Ping He; Xiaozhen Ma; Kai Zhang; Heng Li; Haoyang Mi; Xing-Zhong Xiong; Zuxin Li; Yangmin Li (IEEE Access)
Retracted.